Waqf Based Education Independence In Making Islamic Education Institutions Quality - Eddy Saputra (Yayasan Ilomata, 2021)
Education should be easily accessible for every child of the nation. There are still problems in the world of education, especially for people with low income. The potential of waqf is being promoted and developed in this country. However, it is unfortunate that the new funding has been allocated only as a boost to state finances, and the Indonesian Waqf Board has distributed it to the Ahcmad Wardi Eye Hospital in Serang, So through this research, the researcher proposes that the Indonesian waqf body also participate in developing a national scale Islamic education that can be accessed by anyone. like a quality Islamic education institution such as Al Azhar in Cairo and so on, where these educational institutions become large because of the independence of the institution that is financed by waqf. This research uses descriptive qualitative method. This research was conducted in order to aim for educational institutions to become independent through the empowerment of waqf.